Development of a Loop-Mediated Isothermal Amplification Assay Coupled With a Lateral Flow Dipstick Test for Detection of Myosin Binding Protein C3 A31P Mutation in Maine Coon Cats - Sukumolanan, Pratch; Demeekul, Kanokwan; Petchdee, Soontaree (Frontiers in Veterinary Science, 2022)
Background: Myosin-binding protein C3 A31P (MYBPC3-A31P) missense mutation is a genetic deviation associated with the development of hypertrophic cardiomyopathy (HCM) in Maine Coon cats. The standard detection of the MYBPC3-A31P mutation is complicated, time-consuming, and expensive. Currently, there has been a focus on the speed and reliability of diagnostic tools. Therefore, this study aimed to develop a loop-mediated isothermal amplification assay (LAMP) coupled with a lateral flow dipstick (LFD) test to detect MYBPC3-A31P mutations in Maine Coon cats. Materials and Methods: Fifty-five Maine Coon cats were enrolled in this study, and blood samples were collected. MYBPC3-A31P was genotyped by DNA sequencing. Primers for loop-mediated isothermal amplification (LAMP) with a lateral flow dipstick (LFD) test were designed. The optimal conditions were determined, including temperature and time to completion for the reaction. The sensitivity of A31P-LAMP detection was compared between agarose gel electrophoresis (the standard method) and the LFD test. The A31P-LAMP-LFD test was randomly performed on 7 cats (four with the A31P mutation and three wild-type cats). Results: The A31P-LAMP procedure was able to distinguish between cats with MYBPC3-A31P wild-type cats and MYBPC3-A31P mutant cats. The LAMP reactions were able to be completed in 60 minutes at a single temperature of 64 °C. Moreover, this study demonstrated that A31P-LAMP coupled with the lateral flow dipstick (LFD) test allowed for A31P genotype detection at a lower DNA concentration than agarose gel electrophoresis. Discussions: This new A31P-LAMP with a lateral flow dipstick (LFD) test is a successful and reliable assay with a rapid method, cost-effectiveness, and low requirements for sophisticated equipment for the detection of MYBPC3-A31P mutations. Thus, this assay has excellent potential and can be recognized as a novel screening test for hypertrophic cardiomyopathy associated with MYBPC3-A31P mutations in feline.